2022
DOI: 10.1007/s00248-021-01947-w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phyllosphere Microbiome of Wild Tomato Species in Central Peru upon Dysbiosis

Abstract: Plants are colonized by myriads of microbes across kingdoms, which affect host development, fitness, and reproduction. Hence, plant microbiomes have been explored across a broad range of host species, including model organisms, crops, and trees under controlled and natural conditions. Tomato is one of the world’s most important vegetable crops; however, little is known about the microbiota of wild tomato species. To obtain insights into the tomato microbiota occurring in natural environments, we sampled epiphy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 117 publications
6
17
0
Order By: Relevance
“…Inoculation with the Xanthomonas resulted in fewer Firmicutes and Actinobacteria in both cultivars at the end season. Similar findings of disrupting the abundance of Firmicutes and Actinobacteria upon dysbiosis have been reported both in the phyllosphere and rhizosphere (71,78,79). Inoculation also significantly negatively affected the relative abundance of various genera, including Pseudomonas, Pantoea , and Methylobacterium .…”
Section: Discussionsupporting
confidence: 84%
“…Inoculation with the Xanthomonas resulted in fewer Firmicutes and Actinobacteria in both cultivars at the end season. Similar findings of disrupting the abundance of Firmicutes and Actinobacteria upon dysbiosis have been reported both in the phyllosphere and rhizosphere (71,78,79). Inoculation also significantly negatively affected the relative abundance of various genera, including Pseudomonas, Pantoea , and Methylobacterium .…”
Section: Discussionsupporting
confidence: 84%
“…Geographical locations, plant compartment and growing season are among the main ecological factors that shape the microbial communities in natural plants. Despite some research has been conducted on the impact of geographical locations, compartment and short period of time on the formation of microbial communities in natural plants [13,[41][42][43][44], there is still a lack of studies exploring the role of abiotic factors in shaping microbial communities throughout the plants growing seasons over several plant generations. A further question not studied so far is to what extent does the stability of biotic interaction networks are susceptible to abiotic factors?…”
Section: Discussionmentioning
confidence: 99%
“…The second critical process is deterministic, which includes environmental factors and biotic interactions [9]. Apart from these factors, the microbiome can be impacted by sampling time point, geographical location and host genotype [13]. A comparison of root microbiota in various plants (maize, sorghum, and wheat) revealed that these plants had distinct community compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically targeting leaves with infection symptoms throughout these regions, we found that Alternaria spp. are omnipresent on the leaves but that P. infestans was rare or absent (Runge et al, 2022). Taking into account that we and other studies previously found clearly quantifiable differences in resistance against A. solani between and within wild tomato populations (Chaerani & Voorrips, 2006; Stam et al, 2017) we focused specifically on the diversity of Alternaria and closely related fungal genera.…”
Section: Introductionmentioning
confidence: 99%